Regulatory Effect of Secretome-Hypoxia Preconditioned Mesenchymal Stem Cells on TNF-α Level in Streptozotocin-induced Rats - Amellia, Nazzala Luthfin; Antari, Arini Dewi; Nazar, Mohammad Ariq; Husain, Sofian Azalia; Arifin, Naufal Ardjivani (Stem Cell and Cancer Research (SCCR), 2022)
Background: Type 1 Diabetic Mellitus (T1DM) is a well-known autoimmune disease characterized by a specific adaptative immunity against β-cell antigens. Mesenchymal stem cells (MSC) have emerged as potential immunomodulators in a paracrine manner via their bioactive soluble molecules that involve inflammation-related diseases, including T1DM. Objective: This study aims to investigate the effect of SHMSCs on regulating TNF-α concentrations in STZ-induced rats. Materials and Methods: This study uses a post-only control group design and randomized system that was conducted from December 2022 until January 2023. To induce T1DM-like rats, an intraperitoneal injection (65 mg/kg BW) of streptozotocin (STZ) was inducted. 15 male Wistar rats were subdivided into the following groups: STZ, STZ with 0.5 cc SHMSCs (Low-dose), and STZ with 1 cc SHMSCs (High-dose). The animals received an intraperitoneal injection of SHMSCs once a week for up to 4 weeks. On day 28, the animals were terminated and ELISA measured TNF-α concentrations. Results: After SHMSCs administration, the level of TNF-α in the treated group was decreased in either low-dose or high-dose groups compared with the STZ group. Conclusion: Administration of secretome-hypoxia MSCs may regulate TNF-α concentrations in STZ-induced Rats.